Total vascular isolation in segmental liver resection for echinococcal cyst: case report - D. Hewage, Tharushi Malshani; A. Gamage, Lithmi Viboda; Sergeevich, Belyuk Konstantin (International Surgery Journal, 2025)
Liver echinococcosis is a widespread parasitic disease that does not tend to decrease in endemic regions. High frequency of complications, reaching up to 57%, relapses of the disease, accompanied by repeated surgeries, leave the problem relevant at the present time. The main purpose of the work is to improve the results of treatment of patients with echinococcal liver cysts. This article presents, the outcomes of surgical interventions in two patients, with echinococcal liver cysts who underwent segmental liver resections of the liver, employing total vascular isolation (TVI) technique, which is carried out at the department of pancreatology hepatology and transplantation of organs and tissues, Grodno regional clinical hospital in Grodno, Belarus. Our entire team performed segmental liver resection of echinococcal cysts using the technique of TVI for the both patients who presented with symptoms of abdominal discomfort in their right upper quadrant and further imaging studies confirmed the presence of cystic lesions within the 6 and 7 liver segments, intricately intertwined with major hepatic vessels. Both the patients had optimal surgical outcomes with minimal intraoperative blood loss while preventing major complications including air embolism, with the employment of the method of TVI. The use of the method of TVI allows to significantly reduce intraoperative blood loss, and also makes it possible to avoid extensive resections in echinococcal liver cysts.